Descriptions of Larvae of D esmopachria Babington (Coleoptera: Dytiscidae: Hydroporinae): The D. vicina Sharp Species Group - Michat, Mariano Cruz (2007)
Larval morphology of the Desmopachria vicina Sharp species group is investigated. For this purpose, the three larval instars of Desmopachria concolor Sharp and Desmopachria punctatissima Zimmermann are described and illustrated for the first time, with an emphasis on the morphometry and chaetotaxy. Both species have the setae LA3, LA4 and LA5 inserted proximally on the prementum and the seta LA10 inserted distally on the second labial palpomere, the two larval autapomorphies that define the genus Desmopachria Babington. They are also characterized by the presence of secondary setae on the ventral surface of the siphon of third-instar larva; this character state is a synapomorphy of Desmopachria + Hyphydrus Illiger. Desmopachria concolor and D. punctatissima are very similar morphologically, suggesting that they could be closely related phylogenetically. Larvae of the D. vicina species group differ from those of the Desmopachria convexa (Aubé) species group in the presence of one additional seta on the dorsal surface of the prementum, the more distal insertion of the seta LA2 on the prementum, and the absence of one of the distal pores (LAb or LAd) on the first labial palpomere.